OPTIMIZING LEARNING THROUGH GAGNE'S THEORY: TEACHING VIDEO ANALYSIS FOR PROSPECTIVE TEACHERS - Syahrial, Syahrial; Asrial, Asrial; Sabil, Husni; Azzahra, Miftahul Zannah; Nawahdani, Ahmad Mansur (LPPM Universitas Jambi, 2024)
This study explores and describes the learning process of elementary school teachers and professional education students through the lens of Gagné's learning theory. Using a qualitative approach with a descriptive method, the research analyzes recorded learning sessions of students enrolled in the program. Data collection involves examining the recorded lessons, and the analysis follows a descriptive qualitative framework. The findings reveal that implementing Gagné’s nine instructional events, particularly goal-oriented and active learning strategies, positively influenced student interaction and comprehension of the material. Although there were variations in the ability to recall prior knowledge, all recordings demonstrated significant efforts in delivering content effectively, providing thorough guidance, and offering constructive feedback to enhance knowledge retention and transfer. This study provides a fresh perspective on applying Gagné’s learning theory in professional education, emphasizing its impact on teacher training. Unlike previous studies that often focus on theoretical aspects, this research offers empirical insights into how Gagné’s instructional events can foster deeper engagement and understanding in real-world classroom contexts. Additionally, the study highlights students' diverse experiences in applying Gagné's principles, offering new strategies for improving teaching methods. The implications suggest that educators in teacher preparation programs can use these findings to design more interactive, structured, and outcome-oriented learning environments, ultimately enhancing the quality of education in teacher training programs.